Buckling and Vibration Behavior of Composite Beam due to Axially Varying In-plane Loads. Issue 1 (April 2021) - Kanade, Sangram Anil; Chinnapandi, Lenin Babu Mailan; Jeyaraj, P; Subramanian, Jeyanthi
Abstract: In this work buckling and vibration behavior of composite beam is analyzed based on the shear and normal deformable beam theory (SNDBT) by using Ritz method. The effects of aspect ratios, boundary conditions, fiber angles on the buckling and vibration subjected to non-uniform axial loads studied in detail. The obtained numerical results in terms of dimensionless fundamental frequencies and dimensionless first critical buckling loads are compared with the results from previous research for convergence studies.